2017
DOI: 10.1073/pnas.1716522115
|View full text |Cite
|
Sign up to set email alerts
|

Daple coordinates organ-wide and cell-intrinsic polarity to pattern inner-ear hair bundles

Abstract: SignificanceEach hair cell of our auditory and vestibular systems transduces stimuli into electrical signals through its mechanosensitive hair bundle. Because the bundle is responsive along only a single axis, its orientation is crucial. Two systems determine hair-bundle polarity: planar cell polarity proteins, which establish axes along which hair cells are oriented, and the proteins Gαi and LGN. Investigating how these two systems are coordinated so that each hair bundle is appropriately aligned, we identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 29 publications
6
64
0
Order By: Relevance
“…In the highly polarized MDCK cells, we observe colocalization with the tight junction marker occludin as well as with the adherens junction marker b-catenin ( Figure 1D). Taken together, these findings demonstrate that a significant pool of the cytosolic protein Daple localizes to cell-cell junctions: this is in keeping with prior observations made by others using ependymal, inner ear and MDCK cells [13][14][15][16][17]. These findings suggest that Daple may physically associate with various junctional complexes to maintain such localization.…”
Section: Daple Is Localized On Cell-cell Junctions In Epithelial Cellsupporting
confidence: 90%
See 1 more Smart Citation
“…In the highly polarized MDCK cells, we observe colocalization with the tight junction marker occludin as well as with the adherens junction marker b-catenin ( Figure 1D). Taken together, these findings demonstrate that a significant pool of the cytosolic protein Daple localizes to cell-cell junctions: this is in keeping with prior observations made by others using ependymal, inner ear and MDCK cells [13][14][15][16][17]. These findings suggest that Daple may physically associate with various junctional complexes to maintain such localization.…”
Section: Daple Is Localized On Cell-cell Junctions In Epithelial Cellsupporting
confidence: 90%
“…As for the relevance of our findings in development, it is noteworthy that mutations in Daple (that eliminate its PBM) have been identified in patients with non-syndromic hydrocephalus and depletion of Daple in animal models lead to hydrocephalus as well as ear/hearing defects [14][15][16][17]40]. Underlying both conditions is a failure to polarize the cells and position the cilia.…”
Section: Resultsmentioning
confidence: 71%
“…A fourth component, dishevelled-associating protein with a high frequency of leucine residues (Daple, encoded by CCDC88C), couples the PCP pathway to the formation of the cellintrinsic planar axis by connecting the PCP protein dishevelled to the cell-instrinsic signaling component Gαi. Mice lacking Daple exhibit misoriented and misshapen staircases of stereocilia, caused by uncoupling of Gαi from the kinocilium (Siletti et al, 2017).…”
Section: Apical Membrane Morphology: the Cell Polarity Program And Mementioning
confidence: 99%
“…A possible mechanism by which intercellular PCP signaling regulates Par3 localization is through Daple, which interacts with both Par3 (10) and the core PCP protein Dishevelled (44). Consistent with this, colocalization of Par3, Daple, and Dvl2 in the OC has been reported (10).…”
Section: Par3 Integrates Multiple Pathways To Regulate Hair Bundle Shmentioning
confidence: 62%
“…Multiple signaling modules of the cell-intrinsic machinery have been discovered, including the small GTPase Rac1 and its effector p21-activated kinase (Pak) (3,4), cdc42 and its downstream effector aPKC (5), as well as LGN-Gαi-dynein (6-9), a complex with an evolutionarily conserved role in mitotic spindle orientation. Recently, Dishevelled-associating protein with a high frequency of leucine residues (Daple) has been identified as another regulator of hair bundle shape and orientation through binding to Gαi (10). It has been suggested that these modules act in concert to provide subcellular landmarks and spatially control cortical capture of centriolar microtubules during kinocilium/ basal body positioning, thereby influencing hair bundle shape and orientation.…”
mentioning
confidence: 99%